LanCL2 Implicates in Testicular Redox Homeostasis and Acrosomal Maturation - Yanling Zhao; Jichen Wang; Shuai Shi; Xinting Lan; Xiangyu Cheng; Lixia Li; Yuanfeng Zou; Lanlan Jia; Wentao Liu; Qihui Luo; Zhengli Chen; Chao Huang (MDPI AG, 2024)
Redox balance plays an important role in testicular homeostasis. While lots of antioxidant molecules have been identified as widely expressed, the understanding of the critical mechanisms for redox management in male germ cells is inadequate. This study identified LanCL2 as a major male germ cell-specific antioxidant gene that is important for testicular homeostasis. Highly expressed in the brain and testis, LanCL2 expression correlates with testicular maturation and brain development. LanCL2 is enriched in spermatocytes and round spermatids of the testis. By examining LanCL2 knockout mice, we found that LanCL2 deletion did not affect postnatal brain development but injured the sperm parameters of adult mice. With histopathological analysis, we noticed that LanCL2 KO caused a pre-maturation and accelerated the self-renewal of spermatogonial stem cells in the early stage of spermatogenesis. In contrast, at the adult stage, LanCL2 KO damaged the acrosomal maturation in spermiogenesis, resulting in spermatogenic defects with a reduced number and motility of spermatozoa. Furthermore, we show that this disruption of testicular homeostasis in the LanCL2 KO testis was due to dysbalanced testicular redox homeostasis. This study demonstrates the critical role of LanCL2 in testicular homeostasis and redox balance.